(untitled) (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2021)
Every year, 10.4 million people get sick with Tuberculosis (TB) and 40 percent of them do not receive treatment care - they are “missed” to identify by the health systems. Missing TB cases is major challenge in fighting the disease; pose a serious threat to global health security. As per World Health organization estimation, in 2018, Afghanistan missed 27 percent TB case notification. Thus we conducted an active case finding through house hold survey from June – November, 2018 in Kabul city, districts of Afghanistan. This descriptive cross sectional study included all the residence of 21 sub-districts in Kabul City Afghanistan. After obtaining written consent, data was collected using a structured questionnaire from all presumptive TB cases. Sputum was collected from eligible participants and tested for AFB, Gene-Xpart and Chest X-ray was done. Standard test algorithm and case categorization was done according to WHO recommendations. Descriptive analysis of demographic, clinical and laboratory data was done. A total of 22,596 participants were included and among them 6740 were eligible. Among them 1614(24.3%) individuals were screened positive to have presumptive TB and 105 (6.5%) had laboratory confirmed TB. Thus the case notification rate was 465 in 100,000 populations. Among the presumptive TB cases, mean age was 38.6 + 18.5 years; 74% were female; 72% were housewives/unemployed; 2.6% were smokers. The case notification rate and the point prevalence showed increase numbers than the actual reports by the Afghanistan National TB program, which signifies the program was missing significant numbers of TB cases. Hence active TB case finding might be an effective approach in terms of case notification in Afghanistan. We recommend extending active community TB surveillance of the country.